Relationship between abundance and diversity of odonates to River Ulu Gombak characteristics / Cheah Khai Sern - Cheah , Khai Sern (2016)
Ecohydraulic is considered to be a new field and yet it is emerging and becoming more distinct recently. Not many research on ecohydraulic model can be found especially those that are using adult odonates as ecological indicator. In this study, adult odonates were chosen as the ecological indicator. Their relationship with water quality status and basic hydraulic characteristic were determined for the use in developing an ecohydraulic model for the upstream of Sungai Gombak. In order to do that, the species of adult odonates were identified and quantified for all three sampling sites. Ecological indices which includes Shannon-Wiener index, Eveness and Simpson’s index were then calculated. The water quality status and the basic hydraulic characteristic were recorded. The water quality status that were tested includes biological oxygen demand (BOD), chemical oxygen demand (COD), total suspended solids (TSS), ammoniacal nitrogen, phosphate, temperature, dissolved oxygen (DO), pH and also conductivity. Discharge rate of all three sites were determined based on the width, depth and velocity of the river. Pearson correlation were used to determine the relationship between water quality status and basic hydraulic characteristic with the adult odonates of each sites. A total of 11 species of adult odonates were identified during the sampling. As for the water quality, the upper stream were tested to be the cleanest while the lower stream were less clean ranging from Class I to Class III. The Pearson correlation shows that some species were significantly related by different factors. Although the relationships between the adult odonates with the water quality status and basic hydraulic characteristic were established, the ecohydraulic model for Sungai Gombak was unable to be developed due to the lack of other factors such as canopy cover and riparian vegetation. Further study on the relationship of each species to these factors should be included in future work.